A phase I study of lenalidomide plus chemotherapy with idarubicin and cytarabine in patients with relapsed or refractory acute myeloid leukemia and high‐risk myelodysplastic syndrome. Issue 12 (19th September 2020) - Saygin, Caner; Larkin, Karilyn; Blachly, James S.; Orwick, Shelley; Ngankeu, Apollinaire; Gregory, Charles T.; Phelps, Mitch A.; Mani, Shylaja; Walker, Alison; Garzon, Ramiro; Vasu, Sumithira; Walsh, Katherine J.; et al.
Abstract: Patients with relapsed/refractory (R/R) acute myeloid leukemia (AML) have poor outcomes and hematopoietic cell transplantation (HCT) is the only curative treatment. New targeted therapies improved survival in select patients with specific mutations, however management of patients without these molecular alterations is an unmet need. We conducted a phase one study of lenalidomide in combination with cytarabine/idarubicin salvage chemotherapy in patients with R/R AML and high‐risk myelodysplastic syndromes. A total of 33 patients were enrolled in the study (30 AML, 3 MDS), and treated at three dose levels with 3 + 3 design. Dose‐limiting toxicity (DLT) was seen in eight patients, including four hematologic DLTs. The most commonly observed non‐hematologic serious adverse events were febrile neutropenia, rash, sepsis and renal injury. Dose level −1, consisting of 25 mg/d lenalidomide D1‐21, 1 g/m 2 cytarabine D5‐8, and 8 mg/m 2 idarubicin D5‐7 was determined to be the maximum tolerated dose. Note, 15/33 (45%) of patients were able to receive pre‐planned 21 days of lenalidomide. Overall, 18 patients achieved complete remission (CR) (n = 14) or CR with incomplete count recovery (CRi) (n = 4) with total CR/CRi rate of 56%. The 1‐year and 2‐year overall survival (OS) were 24% and 10%, respectively. Among responders, 10/18 underwent allogeneic HCT and had a 1‐year OS of 40%. There was no molecular pattern associated with response. These data demonstrate that the combination had clinical activity in R/R AML. This regimen should be further investigated for patients who relapsed after HCT, and as a bridge therapy to HCT. (ClinicalTrials.gov identifier: NCT01132586).